Effect of Rice Husks as Filler in Polymer Matrix Composites - Siti Rabiatull Aisha, Idris; Hardinnawirda, Kahar (Faculty Mechanical Engineering, UMP, 2012)
In this study, rice husks filler polyester composites were produced with rice husks (RH) as filler and unsaturated polyester resin (UPR) as the matrix. Several percentage of filler loadings were used (10, 15, 20 and 25 wt %) in order to gain insights into the effect of filler content on the mechanical properties and water intake of the composites. From the results, the tensile strength of the RH filled UPR composites found to be decrease as the filler loading increase. However, as it increases to 25 wt %, the strength shows moderately increase. As for the young modulus, it shows remarkable increase for 15 wt% of RH and decreasing as the RH continually increase up to 25 wt %. Water absorption test was conducted and the results showed that the composites absorb more water as the weight percentage of RH increased, which attributed to the ability of RH fillers to absorb water.